Numerical Simulation Research on Well Pattern Optimization in High–Dip Angle Coal Seams: A Case of Baiyanghe Block - Wang, Hongli; Zhang, Xiao; Zhang, Suian; Huang, Hongxing; Wang, Jun (Frontiers in Earth Science, 2021)
The Baiyanghe block in Fukang, Xinjiang, China, is rich in coalbed methane (CBM) resources, and several pilot experimental wells have yielded high production. Due to the high dip angle (35–55°) of the coal seam in this area, the lack of understanding of the geological characteristics, the physical properties of coal, and gas–water migration law lead to immature development techniques and poor overall development benefits. We first conducted desorption and adsorption tests on low-rank coal of this area and found residual gas in the coal. We established a coalbed methane desorption model suitable for this area by modifying the isotherm adsorption model. Next, by analyzing the influence of the gas–water gravity differentiation in the high–dip angle coal seam and the shallow fired coalbed methane characteristics in this area, we discovered the leakage of CBM from the shallow exposed area of the coal seam. Given the particular physical property of coal and gas–water migration characteristics in this area, we optimized the well pattern: (i) the U-shaped along-dip horizontal well group in coal seams is the main production well for gas production with a spacing distance of 312 m; (ii) a multistage fracturing well drilled in the floor of coal is for water production; and (iii) vertical wells with a spacing distance of 156 m in the shallow area is to capture CBM leakage. Using numerical simulation and net present value (NPV) economics models, we optimized the well pattern details. Applying our CBM desorption model, the numerical simulator can improve the accuracy of the low-rank coalbed methane productivity forecast. The optimization results demonstrated the following: 1) the cumulative gas production of single U-shaped well increased by 89% with the optimal well spacing, 2) the cumulative gas production of the well group increased by 87.54% after adding the floor staged horizontal well, and 3) the amount of CBM leakage decrease by 67.59%.